Use the power you have : a brown woman's guide to politics and political change - Jayapal, Pramila, 1965- (New York : The New Press, 2020)
-- all Written with passion and insight, Use the Power You Have offers a wealth of ideas and inspiration for a new generation of engaged citizens interested in fighting back and making change, whether in Washington or in their own communities.
Intro -- 1 My Immigrant Story -- 2 Becoming an American, Becoming an Activist -- 3 Why Not Me? Running for Office -- 4 State Senate: A Proving Ground -- 5 Congress: Testing My Theory at the Highest Level -- 6 The Movement Goes to Washington -- 7 Building, Pushing, Surging: The Squad, Pelosi, and Me -- 8 Moral Vision-Immigration -- 9 Moral Vision-Medicare for All -- 10 Moral Vision-The Fight for 15 and the Three Supremacies -- Afterword -- Acknowledgments -- Notes -- Index
Online resource, title from digital title page (viewed on February 19, 2021).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Jayapal, Pramila, -- 1965-; United States. -- Congress. -- House -- Biography; Jayapal, Pramila, -- 1965-; United States. -- Congress. -- House; Women legislators -- United States -- Biography; Legislators -- United States -- Biography; East Indian American women -- Biography; Women immigrants -- United States -- Biography; Progressivism (United States politics); United States -- Politics and government -- 1989-; Electronic books; Femmes parlementaires -- États-Unis -- Biographies; Parlementaires -- États-Unis -- Biographies; Américaines d'origine indienne -- Biographies; Immigrantes -- États-Unis -- Biographies; Progressisme -- États-Unis.; États-Unis -- Politique et gouvernement -- 1989-; Livres numériques.; e-books.; PHILOSOPHY -- Political; POLITICAL SCIENCE / Political Process / Political Advocacy; East Indian American women; Legislators; Politics and government; Progressivism (United States politics); Women immigrants; Women legislators; United States; Since 1989; autobiographies (literary genre); Autobiographies; Biographies; Autobiographies; Biographies; Autobiographies; Biographies